TINJAUAN MULTIDIMENSIONAL RELASI YAYASAN (PENDIDIKAN) KANISIUS DAN KEUSKUPAN AGUNG SEMARANG - Mahardika, Amadea Prajna Putra (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2024)
This paper explores the multifaceted relationship between Yayasan (Pendidikan) Kanisius (YK) and the Archdiocese of Semarang (KAS), highlighting operational and relational challenges within a Catholic educational framework. The method used in this research was a literature study combined with empirical experience and interviews. Based on the author’s experience with YK Cabang Surakarta, the study outlines the foundational mission of YK to provide Catholic education, facing financial instability, declining enrollment, and limited support from KAS. The strained partnership was analyzed through Javanese social philosophy and Michel Foucault’s power dynamics, noting that hierarchical structures and inconsistent communication from KAS hinder YK's effectiveness. The author advocates for synodality through strengthened dialogue and mutual understanding, informed by Ignatian spirituality and Avery Dulles' model of the "servant Church." This approach calls for creative fidelity, where YK and KAS collaborate in decision-making to better address educational and social challenges. The study references theological insights from Evangelii Gaudium and Fratelli Tutti, urging KAS to actively support YK’s mission, especially to serve marginalized communities. In conclusion, the paper emphasizes a "servant church" model to transform the KAS-YK relationship into a partnership that honors both educational and ecclesial commitments. Improved communication and resource-sharing are essential for a sustainable impact, fostering a mission-centered community that aligns with the Church’s social teaching and the needs of Indonesia’s diverse society.